Plasma Protein Biomarkers of the Geriatric Syndrome of Frailty - Darvin, Kayla (Oxford University Press, 2014)
Frailty is a geriatric syndrome associated with physical decline with aging. Using a proteomics-based screening method to screen plasma for potential biomarkers, we previously found inflammatory glycoproteins to be increased with frailty. The purpose of this study was to confirm if plasma levels of these glycoproteins, as well as of interleukin-6, are increased with frailty in a larger sample (n = 65) of community-dwelling older adults. Plasma levels of transferrin, fibrinogen, haptoglobin, and interleukin-6 were determined with enzyme-linked immunosorbent assay. Differences in protein concentrations by frailty status were determined using analysis of variance. Higher levels of transferrin (p < .001), fibrinogen (p < .0001), and interleukin-6 (p = .0035) were associated with frailty status (nonfrail, prefrail, or frail) and frailty score (0–5) in this sample even after adjustment for age and sex. Haptoglobin did not differ by frailty status (p = .05). Our findings largely confirmed the findings of our nontargeted approach that inflammatory glycoproteins are increased with frailty. Future studies should include larger examinations of these associations and consider the potential usefulness of these glycoproteins as biomarkers for frailty.